The Effect of Fish Meal Substitution with Squilla empusa on Reproductive Performance of Local duck - Roesdiyanto, Roesdiyanto (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2004)
A study has been conducted to know the effect of fishmeal substitution with Squilla empusa on reproductive performance of local duck. Randomized Completely Design was applied in this experimental. Ninety-six grower local ducks were divided into six treatments ration. Each treatment was replicated by four replications and consists of four local ducks each. The treatment was P0 = 0 % Squilla empusa and 10 % fish meal, P1 = 2 % Squilla empusa and 8 % fish meal, P2 = 4 % Squilla empusa and 6 % fish meal, P3 = 6 % Squilla empusa and 4 % fish meal, P4 = 8 % Squilla empusa and 2 % fish meal, and P5 = 10 % Squilla empusa and 0 % fishmeal. Parameters observed was reproductive performance consisted of sexual maturity, average egg production and egg weight during 3 months of production period. The result showed that fishmeal and Squilla empusa had very significant by effect (P<0,01) on feed consumption, sexual maturity, egg production and egg weight. It was significant by (P< 0,05) on egg production and weight. It was concluded that substitution up to 4.96 % of Squilla empusa give the latest of sexual maturity (5.8 month); the lowers egg production was at 6 % Squilla empusa; at 10 % Squilla empusa egg weight tended to increase. (Animal Production 6(2): 110-117 (2004) Key Words: substitution, Squilla empusa, reproductive performance